Pengaruh Marketing MIX dan Kepercayaan Konsumen Terhadap Keputusan Pembelian Pada Toko Nurbiana Shop di Kota Palopo - Dhea Puspita Anggreini; Erwina; Rosnida; Enjel Randan; Gilang Prayoga Patalongan; Fidyah Alfanugrah Arvika (Movere Journal, 2025)
This study aims to determine the influence of the marketing mix and consumer trust on purchasing decisions. This study was conducted to determine (1) the influence of the marketing mix and consumer trust on purchasing decisions, (2) the influence of the marketing mix on purchasing decisions, and (3) the influence of consumer trust on purchasing decisions. The population in this study consists of all consumers who made purchases at Nurbiana Shop, with a sample size of 30 respondents. The data collection techniques used in this study are observation, interviews, and questionnaires. These three techniques were chosen by the researcher because they are considered more effective for observing the phenomenon under study. The data analysis technique used was multiple linear regression analysis. The results of the study indicate that, simultaneously, the marketing mix and consumer trust significantly influence purchasing decisions. Partially, the marketing mix and consumer trust also significantly influence purchasing decisions at Nurbiana Shop.